A taxonomic re-evaluation of five stomiiform fish species described by August Brauer (1902) with lectotype designations - Gon, Ofer; Assel, Edda; Anderson, Eric; Maclaine, James (Zootaxa, 2022)
A study of the type series of Stylophthalmus paradoxus and Idiacanthus atlanticus (Stomiidae), and Cyclothone livida, C. obscura and C. pallida (Gonostomatidae), uncovered errors in the synonymy of Idiacanthus and inconsistencies regarding the number of type specimens of the three species of Cyclothone. The syntypes of S. paradoxus were matched with the illustrations of this species in Brauer (1906) and the specimen used in the description was identified and designated as a lectotype of this species. A comparison of these syntypes with specimens of Idiacanthus atlanticus, including its syntypes, and of I. fasciola indicated that S. paradoxus is most likely a junior synonym of I. fasciola. In addition, the research resulted in a reliable way to distinguish between I. fasciola and I. atlanticus and in the identification of the primary type of the latter species. Mismatches were found in the information Brauer (1906) provided about the material he had for the three species of Cyclothone as well as with published data about the type series of these species. It seems that the whereabouts of many of the type series specimens is unknown. We therefore propose that the individual specimens Brauer singled out for measurements in his original descriptions of C. livida, C. obscura and C. pallida be recognized as lectotypes.